Internal Branding and Brand Citizenship Behaviour Among Employees of PKT Logistics Group Sdn. Bhd. - Edmund Edward, Edward (2024)
Internal branding has gained popularity in the marketing fields for years, which includes internal brand communication, brand environment, brand leadership, brand reward, and brand culture as predictors of brand commitment and brand citizenship behaviour. Present study investigates the impact of internal branding practices on employee brand citizenship through the mechanism of brand commitment. Employees' brand citizenship behaviour is thought to have a substantial impact on the success of a service organization's brand; therefore, this study aims to investigate the factors that determine internal branding and brand citizenship behaviour among logistics company particularly in PKT Logistics Group Sdn. Bhd. This study was conducted using Social Exchange Theory (SET) to analyse the direct connection between independent and dependent variables and Social Identity Theory (SIT) to explain the relationship between mediating variables and dependent variables. A total of 263 PKT employees participated in a quantitative survey, and the data was analysed using Smart PLS to confirm the hypotheses. It was discovered that internal branding practices such as internal brand communication, brand culture, and brand reward were found to have a significant positive impact on employee brand citizenship behaviour. However, brand environment and brand leadership were revealed to have no effect on employee brand citizenship behaviour. Furthermore, brand commitment was revealed to mediate the relationship between internal branding practices such as brand culture, brand reward and brand citizenship behaviour. Nevertheless, the findings revealed no mediation effect of brand commitment on the connection between internal brand communication.